Antiseptic Stewardship Biocide Resistance and Clinical Implications - Kampf, Günter (Springer International Publishing, 2018)
VVarious antiseptic agents, such as chlorhexidine, are used for different applications, e.g. in healthcare, veterinary medicine, animal production and household products, including cosmetics. However, not all antiseptic agents provide significant health benefits, especially in some products used in human medicine (alcohol-based hand rubs, antimicrobial soaps). While some products (antimicrobial soaps, surface disinfectants, instrument disinfectants, wound antiseptics) may contain one or more biocidal agents with a comparable antimicrobial efficacy but large differences in their potential for microbial adaptation and tolerance. An increased bacterial resistance has been described for various antimicrobial agents, sometimes including a cross-resistance to antibiotics. The book is the first comprehensive reference resource on antiseptic agents, including their efficacy, natural and acquired resistance, adaptation, and cross-resistance. It also discusses their and appropriate use in terms of a balance between their efficacy and the risk of acquired bacterial resistance / tolerance. Focusing on human and veterinary medicine and household products, it helps readers make informed decisions concerning against antiseptic products based on their composition. The book contributes to reduce any unnecessary selection pressure towards emerging pathogens and to keep the powerful antiseptic agents for all those applications that have a clear benefit (e.g. reduction of healthcare-associated infection).